Sport online shopping - Muhammad Syamil, Md Razif (2018)
Mobile online shopping that more focus on sport utilities are least in Malaysia. The emergence of the mobile online shopping in the past decade has influence the society’s lifestyle. Therefore, seller do not have enough time to deliver product that have been ordered. In this globalization era, it is important for the shoppers to provide a delivery to their customer due to their packed schedule and SOS are providing a freelance driver. The purpose to develop this document are to collect the information for developing Sport online Shopping (SOS). It is also to evaluate the functionality of the system. The methodology that have been use is Rapid application development (RAD) method. This method are be chose because it more suitable for developing mobile application that need not much time. The expected result of this Sport Online Shopping (SOS) is can be one of the sport mobile application that can be use by client and people. Thus, the benefit of this SOS is for people that have busy to the daily work and do not have time to go to the shopping and buy their sport utilities. The technologies that have be used are global positioning system (GPS) and database. The project significance of this SOS are provide an effective way from product ordering to feedback.